EXTRINSIC MOTIVATION OF ENGLISH TEACHER IN TEACHING AND LEARNING PROCESS AT SMAN 4 KOTA SOLOK - Kristian Burhan; Yona Syaida Oktira; Helfany Amsa (JURNAL EDUSCIENCE, 2022)
This research aimed to analyze teachers’ extrinsic motivation in teaching and learning process. This research was descriptive research. In this research, this research used participant as the sample, the participant of this research was all of English teachers in SMA Negeri 4 Kota Solok. This research, the used three instruments to find the data, they are questionnaire, interview, and field-note. There are some results of this research; it can be concluded that teacher’s extrinsic motivation: first, the participants’ response, they were allowed to work independently, their school environment was conducive and it make them be comfortable. Second, the participants enjoy with their work, they were satisfied with their job, and they have good relationship with their manager and their students. Third, the participants were satisfied with their fringe benefits, they were satisfied with current salary, they had a job in which they could perform to the best their ability, and they would like to receive more feedback about their teaching from their manager and supervisor. Fourth, the participants would like rules and procedures at work to be clearer, the course material that they use offers variety in terms of activities and task, and they would like more involvement in the process of setting their students’ learning goal. Keyword: teaching and learning process, motivation, extrinsic motivation